2001
DOI: 10.1056/nejm200106213442507
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus and Parainfluenza Virus

Abstract: PATHOGENESISAfter an incubation period of two to eight days, RSV and parainfluenza virus replicate in the nasopharyngeal epithelium, with spread to the lower respiratory tract one to three days later. The characteristic inflammation of RSV bronchiolitis is necrosis and sloughing of the epithelium of the small airways, with edema, and increased secretion of mucus, which ob-The New England Journal of Medicine Downloaded from nejm.org at UNIVERSITY OF TENNESSEE -KNOXVILLE on September 15, 2014. For personal use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
903
2
36

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,058 publications
(984 citation statements)
references
References 86 publications
27
903
2
36
Order By: Relevance
“…Indeed, at our program, transbronchial biopsy at the time of viral infection was performed in 22 patients and 18 (82%) had evidence of acute allograft rejection (13). Perhaps the activation of the immunological mechanism leading to allograft rejection is related to biologically active cytokines, including interleukin (IL)-6, IL-8 and tumor necrosis factor-a elaborated by respiratory epithelial cells and different leukocyte populations when exposed to paramyxovirus (16). More importantly, pathology follow-up surveillance data during 18 months after the parainfluenza virus infection revealed that 32% of the lung transplant recipients developed active bronchiolitis obliterans (OB) (13).…”
Section: Allograft Complicationsmentioning
confidence: 99%
“…Indeed, at our program, transbronchial biopsy at the time of viral infection was performed in 22 patients and 18 (82%) had evidence of acute allograft rejection (13). Perhaps the activation of the immunological mechanism leading to allograft rejection is related to biologically active cytokines, including interleukin (IL)-6, IL-8 and tumor necrosis factor-a elaborated by respiratory epithelial cells and different leukocyte populations when exposed to paramyxovirus (16). More importantly, pathology follow-up surveillance data during 18 months after the parainfluenza virus infection revealed that 32% of the lung transplant recipients developed active bronchiolitis obliterans (OB) (13).…”
Section: Allograft Complicationsmentioning
confidence: 99%
“…It is an important cause of severe respiratory disease in children, particularly those at high risk of acute lower respiratory tract infections 2, 3. RSV is also common in adults, especially the elderly and other high‐risk groups such as those who are immunocompromised 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, RSV infection is the most common cause of respiratory disease leading to hospitalization in children, costing an estimated $300-$400 million annually [1,2]. RSV is the major cause of bronchiolitis in children, and the incidence of bronchiolitis hospitalization in children under 1 year of age increased 2.4-fold from 1980 to 1996 [3,4].…”
Section: Introductionmentioning
confidence: 99%